Optimalisasi Proses Kerja melalui Intervensi Ergonomi dan Rekayasa Material Handling: Studi Kasus Peningkatan Efisiensi dan Kenyamanan Pekerja di CV. Adi Makmur Metalindo - Vidi Agung Fragastia; Yuli Setiawannie; Alan Akbar Bukhori; Khairul Albani (Yayasan Literasi Sains Indonesia, 2025)
This community service activity was conducted at CV Adi Makmur Metalindo, a metal manufacturing company specializing in the production and assembly of palm oil machine components. The program aimed to address two main issues faced by the partner: the high time and cost of material handling, and the low levels of comfort and safety at work due to non-ergonomic working postures. The company’s production process is physically intensive and has yet to fully implement ergonomic principles in workplace design. The activity took place on April, 2025, in the form of a training and assistance session involving 12 participants. The method consisted of interactive lectures, discussions, hands-on simulations, and pre- and post-tests to assess participants' understanding. Results showed an increase in the average test scores from 54.2 to 82.5 (a 52% improvement), a 17.1% reduction in material handling time, and a decrease in REBA scores from 9.0 to 5.5, indicating a significant improvement in working posture. The application of basic ergonomic improvements such as layout adjustment and the use of assistive tools encouraged greater efficiency and workplace comfort. This program demonstrated that ergonomic education can be an effective and practical solution for medium-scale industries aiming to improve productivity and occupational safety.